IMPLEMENTASI KONSEP “JUST IN TIME” PADA LAYANAN BPHTB SECARA ELEKTRONIK PADA BADAN PENDAPATAN DAERAH PEMERINTAH PROVINSI DKI JAKARTA - Eddy Supriadhi; Sapto Budi Santoso; Inayatilah Haerudin; Muhamad Wahrudi; Besar Agung Martono (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
BPHTB is a very strategic regional tax for local governments, not only in terms of its contribution to the DKI Jakarta Provincial Government APBD of IDR 6.4 trillion in the 2022 budget, but also its characteristics as a type of regional tax that is directly related to land affairs, namely the fulfillment of basic rights humans will space to live, live, and move. The extent of the impact of this type of tax makes the policy of taking this type of tax very careful, taking into account various aspects and taking into account the financial risks in selling Regional Original Revenue. In connection with the authority of the Regional Government in collecting BPHTB based on Regional Regulation Number 18 of 2010 concerning BPHTB, this journal presents a comprehensive review of the process of transforming business services and electronic collection of BPHTB at the Regional Revenue Agency of the Provincial Government of DKI Jakarta.